It's a Bird, It's a Plane, It's Superman! Using Mass Media to Fight Intolerance - Alex Armand; Paul Atwell; Joseph Gomes; Giuseppe Musillo; Yannik Schenk (Institute of Labor Economics (IZA), 2024)
This paper investigates the role of mass media in shaping racial tolerance and advancing civil rights in the post-WWII United States. We study the first attempt in the history of mass media to use a radio broadcast targeted at children to promote an inclusive American society. In 1946, amid persistent racial divisions, the popular radio series The Adventures of Superman launched Operation Intolerance, a sequence of new episodes promoting equality, rejecting racial discrimination, and exposing the KKK's bigotry. Using digitized historical data on U.S. radio stations and state-of-the-art radio propagation models, we compute geographic exposure to the broadcasts. Exploiting exogenous exposure to the broadcasts, we employ a cohort study design to analyze individual-level data from 1964 to 1980–a crucial period for civil rights activism and legislation in the United States. We find lasting impacts on those exposed as children, including increased support for civil rights, improved interracial relations, and more progressive political attitudes. These effects translate into greater alignment with the Civil Rights Movement, evidenced by increased support for protests and diminished institutional trust, and further manifested by reduced participation in the Vietnam War. Additionally, county-level panel data illustrate how areas covered by the broadcast in 1946 evolve towards less segregationist attitudes, a lower presence of the KKK, and an increase in civil rights activism and prominence in discourse.
Keywords: D7; D83; I24; J15; L82; N32; 330; mass media; radio; segregation; Ku Klux Klan; superman; intolerance; civil rights; racism; protest